DEVELOPMENT OF STAD TYPE COOPERATIVE-BASED WORKSHEET FOR JUNIOR HIGH SCHOOL ON VIBRATION AND WAVE MATERIALS - Sari, Mailinda; Nurhayati (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2024)
Science learning emphasizes process skills in students, one of which is being able to interact and collaborate between students. This is a component of 21st century learning. The purpose of this development research is to develop LKPD based on the STAD Type Cooperative Learning model on grade VIII Vibration and Wave material. The development model used is the ADDIE development model. The research instrument used is a validation sheet, student response questionnaire, posttest questions for vibration and wave material. The subject of this research is a Cooperative-based LKPD of STAD Type developed at SMPN 2 Diwek Jombang. The development process of Cooperative-based LKPD goes through 5 stages, namely: Analyze, Design, Development, Implementation, and Evaluation. The results of LKPD research based on the STAD Type Cooperative learning model show that the validity of LKPD and Vibration and Waves material got an average score of 3.93 with a valid category. The results of practicality get a percentage of 90% with the category of very practical, and a percentage of 87,5% for effectiveness with the category of very effective